Perceived Organizational Support and Resilience as Predictors of Employee Engagement among Digital Marketing Employees in Purwokerto - Tri Sukmaeni; Rosita Endang Kusmaryani (Da'wa Faculty of Islamic State University Salatiga, 2025)
Digital marketing companies face challenges in maintaining employee engagement amidst the demands of technological change. Although career development programs are available, some employees still show suboptimal engagement. Previous studies have shown that perceptions of organizational support and resilience play a crucial role in enhancing employee engagement. Therefore, this study aims to examine these two factors as predictors of employee engagement in digital marketing companies. The approach used in this study is quantitative, employing a survey research design, and the study utilized a sample of 144 employees. The sampling technique used in this study is Random Sampling. The instruments used are the Employee Engagement Scale, a psychology scale of 12 items; the Perceived Organizational Support Scale, an instrument of 9 items; and resilience, using the CD-RISC-10 of 10 items. The results of the study showed that perceptions of organizational support and resilience have a significant effect on employee engagement, with a significance value of 0.000 (<0.05). The higher an employee's perception of the support provided by the organization, and the higher their level of psychological resilience or endurance, the higher their level of employee engagement in their work. These findings highlight the significance of psychological factors and organizational support in promoting work engagement in a dynamic and competitive work environment.